PERSEPSI TERHADAP UKURAN TUBUH DENGAN STATUS GIZI REMAJA PUTRI DI KOTA PALANGKA RAYA - CIA APRILIANTI (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2013)
Background: Nutritional problems can occur to all phases of life, including in adolescence. A perception on body shape or size is considered a cause of unhealthy eating habit in adolescents. This wrong perception is then followed by food consumption limitation, avoiding certain kinds of food without paying attention on nutrition standard and health which finally leads to under nutrition caused by insufficient energy and iron intakes. Health status will decrease in an individual with underweight, overweight, and obesity statuses compared to that with normal nutritional status. This was an observational study with a crosssectional study design. In this study, the measurement of the independent variable (perception on body shape) and the dependent variable (nutritional status) is done to 134 female students of senior high schools in Palangka Raya Municipality. The prevalence of adolescent girls experiencing nutritional problems either under nutrition or over nutrition was 48.5%. There was a relationship between a perception on body shape and adolescents’ nutritional status. In adolescents with perception in disagreement with their body shape, they had a onetime greater chance of experiencing underweight (95% CI: 0.42-2.35) and a 3.9 time greater chance of experiencing overweight (95% CI: 1.59-9.64). In representing their body shape, adolescents tend to experience overestimation and underestimation. In this adolescent group, a prevalence of greater nutritional problems is more likely to be found.